Pengaruh Sosialisasi Literasi Keuangan Otoritas Jasa Keuangan Terhadap Perilaku Keuangan: Pada Mahasiswa Universitas Nusa Cendana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of financial literacy socialization conducted by the Financial Services Authority (OJK) on the financial behavior of students at Universitas Nusa Cendana. Utilizing a survey method and data collection through questionnaires, this research examines the extent to which students' understanding and knowledge of financial literacy influence their financial decision-making and behavior. The findings of this study are expected to provide valuable information for educational institutions, government bodies, and financial organizations in designing more effective financial literacy programs. Additionally, this research aims to offer recommendations for enhancing financial literacy among students, enabling them to manage their personal finances more effectively.